Analysis of family network for woodcarving handicraft entrepreneurship in Vietnam - Tran Thi Nhu Ngoc; Routray, Jayant Kumar; Ahmad, Mokbul Morshed; Soni, Peeyush; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2016)
In rural Vietnam, the community cohesion and the inextricably linkage in the family network are the foundation for social -economic development and the existence of the villages. Along with the traditional culture of villages, traditional wood carving handicraft villages were developed strongly in long time of country history. In recent years, the competition is increasing due to the industrialization and globalization, the handicraft villages in general and wood carving handicraft villages in particular are facing many challenges. Family network can promote the venture development through providing of resources with lower costs and risks and help individuals facing risks and vulnerability when they work in market. On other hand, it also can encumber the entrepreneurship development by the overlapping and inward-focused networks. Keeping in view the potential importance wood carving in the context of rural development, source of employment and revenue generation for the families this study has been designed; to identify and analyze the family network of woodcarving enterprises, to study the practice and function of family network in the production and marketing activities, to measure the contribution of family network system in terms of enterprise{u2018}s benefits also to discover the advantages and limitations of family network influence on enterprises and know about strategies adopted for the enhancement of enterprise. The data were collected from 78 enterprises and 16 case studies. A standardizes questionnaires for structured interview combined with key informant interview were adopted for data collection. The data composed of both qualitative and quantitative. A multistage sampling was techniques was employed to select the respondents. Firstly, the study area was purposely chosen due to its importance in wood carving enterprise. Secondly, the enterprises were randomly selected the list of enterprise lists provided by commune head. For data analysis, the study has employed, Chi-square, paired T-Test, Fisher-Exact Test and ANOVA. The results of the findings showed that, most of respondents have the medium size of family network. The results of the Chi-square Test showed that the distribution of family network size among types of enterprises is statistically different. Group of medium-scale enterprises had more family network members than other group. Key members in family network were parents, partner, children, sibling and cousin of both entrepreneurs and partners. These all belonged to nuclear family members, paternal kin and people who were the same generation with entrepreneurs. Main compositions of family network distribute into production or both production-marketing network. However, the findings also reflect that there were some implicit rules existed in study area among family members regarding business, such as keeping secret in sharing the special products and customers among family members, and priority in sharing the opportunities of work for family members. Trust was the one of the most important factor in relation among the members of the family network.Results of the family network showed that it has played an important role in all the contents of business processes, especially in production. The free provision was very important for entrepreneurs when they established their own enterprises and when they faced risks. In addition, this, family network members could cooperate and provide service to entrepreneurs to develop their enterprises. The distribution of respondents in three groups of enterprises in almost contents of supports were significantly different. In production network, the proportion of medium and large enterprises had cooperated with family members was more than small enterprises. The findings of the family network revealed that the family network provided many benefits in supporting for woodcarving entrepreneurs, both in direct and indirect aspects. The family network{u2018}s help contributed the sources for entrepreneurs, reduced the cost of hired labor, and improved their technical, managerial skills and decision-making. The study further explored that industrialization, modernization and globalization were the opportunities and the threats for enterprises and family network. The findings for entrepreneurs{u2018} strategies that were adapted with difficult business condition by different ways. Particularly, when the entrepreneurs faced difficult time in business, they applied strategies that reduced to reduce the risks. Based on findings of the study, as the entrepreneurs lacked the modern knowledge. Therefore, rural development policy and program could prefer the family network as an important capital to exchange the knowledge and skills.The design of training program should combine formal and informal training with the involvement of artisans. Entrepreneurs should retain and expand their family network with the strong connection to extended family members without exception of blood and non-blood relation, maternal and paternal relation for any risk mitigation.The entrepreneurs should expand business network with people from outside village and in potential markets. Moreover, the involvement of cooperative can also help in the enhancement of the wood carving industry. Hence, the family network is playing a significant role in wood carving industry around the world, where the Vietnam has no exemption.
A research submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Research studies project report (M.Sc.) - Asian Institute of Technology, 2016
Keywords: Wood-carving -- Technique; Handicraft -- Vietnam